2020
DOI: 10.1097/corr.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

What Demographic and Clinical Factors Are Associated with In-hospital Mortality in Patients with Necrotizing Fasciitis?

Abstract: Background Necrotizing fasciitis is a rare infection with rapid deterioration and a high mortality rate. Factors associated with in-hospital mortality have not been thoroughly evaluated. Although predictive models identifying the diagnosis of necrotizing fasciitis have been described (such as the Laboratory Risk Indicator for Necrotizing Fasciitis [LRINEC]), their use in predicting mortality is limited. Questions/purposes (1) What demographic factors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Amputation rates in previous studies ranged from 14% to 26%. 7,11,[15][16][17] Some of the variables identified that were associated with increased amputation risk were older than 60 years, diabetes, sepsis, systolic blood pressure less than 90 mm Hg at admission, heart disease, transfer status, chronic wound as etiology, sodium less than 130 mEq/L, male sex, and non-White ethnicity. 11,12,18 Jansen-Winkeln et al 3 found the diagnosis of NSTI primarily clinical and that a regimen of clindamycin, gentamicin, and penicillin provides satisfactory coverage against 95% of causative pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amputation rates in previous studies ranged from 14% to 26%. 7,11,[15][16][17] Some of the variables identified that were associated with increased amputation risk were older than 60 years, diabetes, sepsis, systolic blood pressure less than 90 mm Hg at admission, heart disease, transfer status, chronic wound as etiology, sodium less than 130 mEq/L, male sex, and non-White ethnicity. 11,12,18 Jansen-Winkeln et al 3 found the diagnosis of NSTI primarily clinical and that a regimen of clindamycin, gentamicin, and penicillin provides satisfactory coverage against 95% of causative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…12 Interestingly, mortality in patients with diabetes was found to be substantially lower (8.5% vs. 16.5%). 9,12,17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard of care is emergency surgical intervention with massive debridement of all necrotic tissues and broad spectrum antibiotherapy. Mortality rates are high, currently even with the most recent advances in medicine mortality is around 20% and is touching 100% in the absence of immediate medical intervention [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of bullae showed a moderate positive correlation with amputation and mortality rate, suggesting that this symptom reflects a turning point in the prognosis of the disease. 3 1 The First Affiliated Hospital of Nanjing Medical University, Nanjing, China…”
mentioning
confidence: 99%